Cerebral oxygenation during cortical activation: The effect of three exercise training modalities - Terblanche, E.; Coetsee, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduaction: Research on the influence of exercise training on cerebral oxygenation patterns is inconsistent and not well understood. Physical training induces structural brain changes as well as functional changes in neural networks essential for cognitive processing. It is, however, uncertain how the changes relate to cognitive performance and it remains to be established if these patterns are training mode dependent. The primary aim of this study was to determine if the exercise training mode has a differential effect on older individuals` cerebral oxygenation during cortical activation. Methods: Sixty seven inactive individuals (55 to 75 years) volunteered for this intervention study. Participants were allocated to a resistance training (RT) group (n=22), high-intensity interval training (HIIT) group (n=13), moderate continuous training (MCT) group (n=13) and a control (CON) group (n=19). Each training group performed three supervised exercise sessions per week for a period of 16 weeks. Near-infrared spectroscopy (NIRS) was used to measure cerebral oxygenation during a simple and complex cognitive task. Data were analysed using mixed model repeated measures ANOVA and P < 0.05 was considered statistically significant. Cohen`s effect sizes were calculated to compare the magnitude of differences in outcome variables between the groups. Results: CON showed higher relative O2Hb values during the simple and complex Stroop tasks during post-test (ES = 0.76 and 0.62, respectively; P < 0.05). MCT showed a decrease in O2Hb on the simple (ES = 0.48; P > 0.05) and complex (ES = 0.50; P > 0.05) tasks. The HIIT groups` O2Hb on the simple task decreased from pre-test (ES = 0.45; P > 0.05). MCT showed an increase in HHb on the simple (ES = 0.89; P < 0.05) and complex (ES = 1.14; P < 0.05) cognitive tasks. HIIT exhibited a smaller decrease in the concentration of HHb compared to pre-test measurements on the simple (ES = 0.67; P > 0.05) and complex tasks (ES = 0.49; P > 0.05). The RT group did not show any significant changes in their activation patterns during the simple or complex task when comparing pre- and post-test values (ES < 0.3; P > 0.05). Discussion: Sixteen weeks of high-intensity interval training and moderate continuous aerobic training improved task-efficient cerebral oxygenation and oxygen utilization during cortical activation in older individuals more than resistance training. These findings may reflect the different neural-cognitive mechanisms involved with different modes of exercise training. It has been suggested that aerobic training is linked to elevated levels of BDNF, while resistance training produces increased levels of IGF-1. However, it is unclear whether these differences account for the varying responses in cerebral oxygenation observed in this study.